Bacterial Colonies in Cervicovaginal Mucosa of Normal Spontaneous Intraoperative Delivery Patients 15 to 41 Years Old - Masangkay, Frederick R. (Asian Journal of Biological and Life Sciences, 2015)
To identify common organism colonizing the cervico-vaginal mucosa of normal spontaneous intraoperative delivery patientsswabs were collected from 50 subjects prior to child birth. Swabs were used for Gram-stained slide preparation and bacterial cultures. Swabs for culture were placed in Thioglycollate broth, incubated at 350 C for 24 hours and streaked on Blood agar plates (BAP). BAPs were incubated at 350 C for 24 hours.Colonies yielded 97 bacterial and 1 fungal isolates. Bacteria isolated wereLactobacilli spp. 36 (36.73%), E. coli 19 (19.31%), CoNS 17 (17.35%), S. aureus 13 (13.27%), K. pneumoniae 11 (11.22%), P. mirabilis 1 (1.02%). Multiple colonies of organisms were observed; infected subjects yielded higher rates of multiple colonization 8 (40%) withE. coli and S. aureus found to be predominantly co-infecting subjects with greater than 10 pus cells LPF. Microscopic evaluation of pus cells were insufficient to rule out bacterial colonization highlighting the importance of culture methodologies. Multiple colonization of organism suggests molecular influences on growth and biofilm formation aside from specie to specie interaction. Application of 2% erythromycin bath suggests inhibition ofcolonization of infants after birth therebynegating the formation of inflammatory response. These data can provide information for maternal prophylaxis and post-delivery infant management.
Keywords: Coagulase-negative Staphylococci; Erythromycin; Escherichia coli; Pus cells; Streptococcus agalactiae